The Essence of Business Management and Entrepreneurship in the Nigerian Marketing System - Ohazulike , Leo Atuchukwu; Nkoli , Chendo (African Journal of Education,Science and Technology (AJEST), 2013)
This paper scrutinizes the essence of business management and entrepreneurship in the Nigerian marketing system. Entrepreneurship is interchangeable with business practice. Business management is the decisions and directives applied by the individual or the owner of the business. It occurs when an enterprising person or groups pursue profitable opportunities or lucrative business opportunities. The problems that associate with entrepreneurs are unable to receive quality advices and to have a mentor, who had an experience. Finance is also needed. Entrepreneurship is mainly a one man business. Competition is also a problem in the market place. Lack of infrastructure affects the efforts of entrepreneurs. The study sought to identify ways in which business managers or entrepreneurs can raise and obtain initial capital or finance, determine who succeeds or takes over the business because of the uncertainty of life, investigate on how to embark on effective strategies that will check competition, in order to remain in business, identify ways to assist the management to overcome challenges of limited infrastructure and highlight on the recent development that can enlighten the business managers on the latest technology to enhance their competitive advantage. The content of this paper is of great importance to state government, entrepreneurs in Awka and students. Survey research design was applied, sampling plan, analysis of Likert questions and percentage of each analysis was stated. One hundred and twenty respondents duly filled their copies of the questionnaire, and majority strongly agreed to the Likert questions asked.